University smoke-free policies in Australia: lessons for Indonesia - Mentari Widiastuti; Coral Gartner; Sheleigh Lawler (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Background: Eliminating exposure to second-hand smoke is one of the best practices to control noncommunicable diseases. Indonesia has been dealing with growing burdens of noncommunicable disease due to the high and persistent prevalence of tobacco smoking in the country. On the other hand, Australia, a neighbouring country of Indonesia, shows an impressive progress in altering its national tobacco epidemic through the establishment of smoke-free policies. In recent years, Australia has extended its smoke-free policies to higher education institutions. Meanwhile, it is assumed that the scope and implementation of university smoke-free policies in Indonesia are still limited. Objectives: This paper aims to present evidence of Australian university smoke-free policies and to find gaps in the implementation of university smoke-free policies in Indonesia. Findings from an unpublished preliminary cross-sectional study on 100% smoke-free policies at The University of Queensland, Australia were synthesised with published literature on smoke-free policies at other Australian universities and higher education institutions. An online search was also conducted on Google Scholar and PubMed to find evidence of university smoke-free policies in Indonesia. Lessons Learnt: One study indicates that all universities in Australia have implemented smoke-free policies to various degrees. The aim of such policies is to promote wellness rather than to restrict smokers. Research is integral to the development and implementation of university smoke-free policies in Australia. Support from university staff and students, policy enforcement, provision of quit service on campus, awareness-raising, and avoiding stigmatisation of smokers are some important considerations in policy development and implementation. Meanwhile, the implementation of campus smoke-free policies in Indonesian universities is inadequate. The existing evidence is also lacking in quantity and quality. Collaborative efforts involving university stakeholders, researchers, staff, and students are prerequisite to successfully adopt smoke-free policies on university campuses in Indonesia.